Paradoxical Infarction? Inferior STEMI With Unexpected Discovery of ASD in an Oncology Patient: A Case of Combined Percutaneous Intervention - Miguel Angel Balbuena Madera; Juan Francisco Garcia Garcia; Antonio Vargas Cruz; Heberto Aquino Bruno; Jesús Guadalupe González Jasso (Clinical Case Reports)
ABSTRACT This case report explores the management of a 56‐year‐old female oncology patient presenting with acute ST‐elevation myocardial infarction (STEMI) and an incidental atrial septal defect (ASD). The patient, with a history of rectal cancer and hypothyroidism, experienced acute chest pain and dyspnea. She was diagnosed with an inferior STEMI and underwent percutaneous coronary intervention (PCI) with the placement of three medicated stents in the right coronary artery. During hospitalization, an echocardiogram revealed a significant ostium secundum ASD. Angiography indicated thrombi, suggesting a potential paradoxical embolism. Percutaneous ASD closure was performed during the same hospital stay, leading to a favorable clinical course without immediate complications. This case highlights the importance of a multidisciplinary approach and comprehensive evaluation in managing complex cardiovascular conditions, particularly in patients with increased thrombotic risk due to malignancy.